Analysis of the Entrepreneurial Spirit of Students of the Faculty of Economics and Business, Christian University of Indonesia, Through the Theory of Planned Behavioural Approach - F. Sembiring, Carolina; Situmorang, Humala (Sahabat Publikasi, 2025)
This study discusses the entrepreneurial spirit of students for 2 study programs, namely S1-Accounting and S1-Management Faculty of Economics and Business with a research sample of 168 students for the two study programs. given in odd semester (V) only, while for S1 Management study program apart from Entrepreneurship, Business Planning courses are also given (the new curriculum has been changed to the Entrepreneurial Business Creation course) in odd semester. Based on these problems, the purpose of this study was to find out the entrepreneurial spirit of students in the two Faculty of Economics and Business study programs, namely: 1). Analyzing the comparison of personal attitudes in students of the Bachelor of Accounting and Management study programs, 2). Analyzing the comparison of subjective forms in students of the Bachelor of Accounting and Management study programs, 3). Analyzing the comparison of perceived behavioral control in students of the Bachelor of Accounting and Management study programs and 4). Analyzing the comparison of entrepreneurial intentions in students of the Bachelor of Accounting and Management study programs. This research was carried out in the odd semester of the 2022/2023 academic year, and the type of research used was descriptive research, using a survey method with a quantitative research approach. This type of research is descriptive research with a survey method. The results of the study used the Mann-Whitney test analysis, namely that there were significant differences between personal attitudes, perceived behavioral control and entrepreneurial intention, in students of S1-Accounting and S1-Management study programs because they had a p-value <0.05, while for subjective norms in S1-Accounting and S1-Management study program students did not show a significant difference because they had a p-value > 0.05.